Th1 and Th2 immune response to P30 and ROP18 peptides in human toxoplasmosis (2014)
We determined the specific lymphocyte proliferative response and cytokine profile production regarding Toxoplasma P30 (2017 from virulent and non-virulent strain) and ROP18 protein-derived peptides (from clonal lineages I, II and III) in 19 patients having ocular toxoplasmosis, five suffering chronic asymptomatic infection, nine with congenital toxoplasmosis and eight Toxoplasma negative people. A Beckman Coulter FC500 flow cytometer was used for determining antigen-specific T cells (CD3+ CD4+ or CD3+ CD8+ cells) in peripheral blood culture. IFN ? and IL10 levels were determined in culture supernatants. Specific CD4+ and CD8+ T cell response to total antigen and P30- and ROP18-derived peptides was observed in infected people. Ocular toxoplasmosis patients had a preferential Th2 response after antigenic stimulation. Non-virulent peptide 2017 was able to shift response toward Th1 in congenitally infected children and virulent peptide 2017 induced a Th2 response in chronically infected, asymptomatic people. An immune response in human toxoplasmosis after ex vivo antigenic stimulation was Th1- or Th2-skewed, depending on a patient’s clinical condition. Colombian ocular toxoplasmosis patients’ immune response was Th2-skewed, regardless of the nature of antigen stimulus. © 2014, Springer-Verlag Berlin Heidelberg.